Damon technique for orthodontic treatment of a patient with temporomandibular joint dysfunction - Jessica Peñaherrera Bailón; Maria Rodriguez Tates; Rosa C Paredes Coloma; Karol Tates Almeida; Byron Velasquez Ron (Wolters Kluwer Medknow Publications, 2023)
The Damon system is an effective, less-invasive treatment that provides orthodontic dentists with an adequate biomechanical process, offering a reduction in treatment time; patients with temporomandibular dysfunction present even greater complexity in their clinical picture, relying on clinical and radiographic differential diagnoses to facilitate a good prognosis. The objective was to apply the orthodontic treatment (Damon technique) to stabilize patients with temporomandibular dysfunction. The patient with premature loss of the first lower molars (36 and 46) experienced pathological alterations in the temporomandibular joints (TMJs) (bilaterally). The diagnosis was reached using the clinical history of temporomandibular joint disorders (diagnostic criteria) axis II: moderate pain (VAS) in muscles, moderate stress (Hamilton 51/60), lateral and panoramic cephalic radiographs, magnetic resonance imaging of bilateral TMJ, cephalometry, photographs, and models. Treatment with the Damon system is recommended to recover optimal functional occlusion in a short period, followed by referral for oral rehabilitation as an adjunct to the treatment plan. The verticalization of the second molars, maximum optimal intercuspidation, appropriate overbite and overjet, and pain control in the TMJ were evaluated. Stabilization of the disc condyle complex by eliminating interference and premature points of contact providing cervical/cranio/mandibular balance.